Leucine mediates cognitive dysfunction in early life stress-induced mental disorders by activating autophagy - Wang, Xiaotian; Wang, Xue; Xie, Fang; Sun, Zhaowei; Guo, Bomin; Li, Feng; Wang, Shida; Wang, Ying; Tian, Yingrui; Zhao, Yun; Qian, Lingjia (Frontiers in Cellular Neuroscience, 2023)
Early life stress (ELS) is one of the important risk factors for mental illness. Studies have reported that amino acid metabolism is abnormal in the plasma, and changes in parts of amino acids may be an underlying molecular mechanism of mental illness caused by ELS in adults. Herein, we explored the relationship between the amino acids in cerebrospinal fluid (CSF) and cognitive dysfunction in ELS rats. The results showed that MS rats were more prone to cognitive impairment than controls. Nissl staining showed that the number of neurons in the CA1 and CA3 regions of the hippocampus significantly decreased in MS rats. Compared to controls, leucine levels were decreased in the CSF of MS rats and highly correlated with the number of hippocampal neurons. It was found that a low-leucine diet can aggravate the cognitive dysfunction caused by MS, and leucine supplementation can improve the degree of stress-induced cognitive impairment. The autophagosomes in the hippocampus of rats were detected by a transmission electron microscope. The data found that there were autophagosomes in the hippocampus of the low-leucine diet rats of the CON and MS group but not in the high-leucine diet MS group. The expression of Beclin-1 in the hippocampus was significantly increased in the MS normal diet group and MS low-leucine diet group and decreased in the MS high-leucine diet group compared with the MS low-leucine diet group. Meanwhile, the BCL-2/Bax ratio was significantly decreased in the normal low-leucine diet group, MS normal diet group, and MS low-leucine diet group. Leucine deficiency could activate neuronal autophagy, including enhanced LC3II/LC3I and mRFP-GFP-LC3, which was consistent with the in vivo results. Moreover, the cell apoptosis rate and LDH cytotoxicity were increased with leucine deficiency. In conclusion, MS leads to a decrease of leucine content in the rat CSF, which may mediate the excessive activation of autophagy in hippocampal neurons to induce neuron damage and apoptosis and then result in cognitive impairment. Abnormal autophagy may be an important pathological mechanism of cognitive dysfunction induced by ELS, and leucine may be regarded as a potential pharmacological target for improving mental health status.